Estudio prospectivo del sistema de evaluación para el ascenso de los oficiales de la Policía Nacional al año 2030. - Vaca Belalcázar, Henry Santiago (2021)
The evaluation system for police promotion is a means of vital relevance for the development and future projection of the National Police of Ecuador. Since, it enables the promotion or dismissal of police officers at different hierarchical levels. Currently, this system is being managed with high levels of subjectivity and discretion by the authorities responsible for rating. It should be added that the assessment approach is directed more towards conjunctural relationships than meritocracy. These dilemmas have caused a low-context work environment at the institutional level, which has led to divisions and power struggles in different promotions. These facts affect individual performance, institutional performance and therefore the service provided to the community, which is the end user of police work. The objective of the study is to design the desirable scenario and the strategic action routes that facilitate the construction of an efficient, equitable and ethical evaluation system for the promotion of police officers; that strengthens the organizational culture and the police doctrine, and at the same time increases the collective performance of the National Police of Ecuador to the year 2030. For which, the research was developed based on the voluntary current of the studies of the future, specifically the postulates theoretical, methodological and instrumental studies of the French school of prospective, which is based on the analysis: systemic, multidisciplinary, voluntarist (future can be built) and of multiple possible and desirable futures for the object of study, through the application of several prospective techniques proposed by professors Michel Godet and Francisco Mojica. The most relevant results of the research were obtained from the statistical analysis of the data from the evaluation system for promotion (2010-2020 period), which made it possible to demonstrate what was argued in the problematic situation of the study. Likewise, through the application of prospective workshops to focus groups and the Mic-Mac software, it was possible to identify the key variables of the system, that is, those that would mark its future evolution. On the other hand, through the application of prospective workshops to focus groups and the Mactor software, the dominant actors of the system, the convergences and divergences between actors and their positions regarding the challenging objectives proposed from the key variables were identified. It should also be said that through surveys and the Smic-Prob-Expert software, it was possible to identify three probabilistic scenarios (one probable scenario and two alternative ones) for the promotion evaluation system, among which the desirable scenario can be mentioned. Finally, through the application of prospective workshops to focus groups and the IGO tool (importance and governance), the strategies that would allow the achievement of the desirable scenario for the evaluation system for promotion to the year 2030 were built.